Dynamic model of hard disk drive (HDD) latch system - Lum, Jin Xian. (2009)
The goal of this project is to develop a HDD collision model, and from this model create a simulation tool to predict the impact response of the Head Actuator Assembly (HAA) when a load/unload (L/UL) type Hard Disk Drive (HDD) undergoes a drop test. In the event when the HDD is dropped against a hard surface, the impulse experienced by the HAA may cause it to lift off the ramp and land on the surface of the disk. Under these circumstances, the HDD may fail instantly or degrade over time. Various latch mechanism designs have been introduced to counteract this problem. However, there will still be instances when the latch mechanism fails to engage the HAA. Therefore, the ability to predict the impact response of the HAA is critical in improving the shock robustness of the HDD.